Assessment of the associated factors to the green area’s attendance in a brazilian city: a cross-sectional study - Ribeiro Marques, Valeska; Silva, Luiz Felipe (O Mundo da Saúde, 2016)
Green areas (GA) contribute to improving the quality of life, can reduce temperature extremes, lessen the perception of noise, retain dust, and increase the permeability of the urban area, offering a nice space for physical activity and social interaction between many other benefits. It is a space that behaves as a promoter of health. The aim of this study was to evaluate which variables are associated with the GA attendance in Mogi Mirim, SP. It was conducted a cross- sectional study to verify the values of the Odds Ratios of significant variables associated with the GA attendance. Data were collected by random sampling of households, through structured questionnaire to 262 adults, between February and August 2012. The technique applied was logistic regression to describe the association between the dependent variable, AV attendance at least once a week and the set of explanatory variables. Of the respondents, 47% of the sample attends GA, at least once a week. Variables that showed significant positive association with the GA use were: have a dog (OR = 1.88; 95%CI: 1.13 – 3.15) and, own garden at home (OR = 1.83; 95%CI: 1.08 – 3.11. The variable that showed a significant negative association was use the bus as a primary means of transportation (OR = 0.51; 95%CI: 0.29 – 0.89. This research explored and presented a research methodology for assessing the socioeconomic characteristics of the population and possible associations with use of GA. Thus, it is an important resource, little found in the national literature, which must be replicated in order to stimulate this essential practice of health promotion..